Hubungan Intensitas Kebisingan Dan Lama Kerja Dengan Kejadian Hipertensi Pada Tenaga Kerja Bagian Produksi PT. Japfa Comfeed Indonesia Tbk. - Andry Setiawan; Yohanes Joko Supriyadi; Maharso Maharso (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
The Relations Of The Intensity Of Noise And Work Term With The Hypertension Case Of The Production Parts Employees In PT. Japfa Comfeed Indonesia Tbk.. Some research results prove that one of the risk factor of stroke is high blood pressure (hypertension). Noise pollution may be associated with the occurrence of hypertention, this is supported by an epidemiological study in the United States. The results of that study mentioned that people exposed to noise tend to have unstable emotions. Emotional instability will lead to a stress. If the stress happened long enough, it will cause the narrowing of blood vessels, so it will make the heart to work harder to pump blood throughout the body. In a long term, blood pressure will rise, and this is called Hypertension. The purpose of this study is to determine the relations between the intensity of noise pollution and work term with the case of hypertension in the production parts employee of PT. Japfa Comfeed Indonesia Tbk. Tanah Laut regency in 2017. The research method used is an analytical survey with cross sectional approach. The population in this study is amounted to 57 people and the sample amounted to 57 people. The results of this study indicates that there is a moderate relationship between the intensity of noise pollution with the incidence of hypertension (p-value = 0,002 < α = 0,05 r = 0,407), and there is a low relationship between work term with the incidence of hypertension (p-value = 0,014 < α = 0,05 r = 0,323). Suggestions given to the company is to provide guidance on the use of PPE, perform routine health checks on employees and rotate the position of work on the employee of production.